2021
DOI: 10.1038/s41421-021-00356-0
|View full text |Cite
|
Sign up to set email alerts
|

Metagenome-genome-wide association studies reveal human genetic impact on the oral microbiome

Abstract: The oral microbiota contains billions of microbial cells, which could contribute to diseases in many body sites. Challenged by eating, drinking, and dental hygiene on a daily basis, the oral microbiota is regarded as highly dynamic. Here, we report significant human genomic associations with the oral metagenome from more than 1915 individuals, for both the tongue dorsum (n = 2017) and saliva (n = 1915). We identified five genetic loci associated with oral microbiota at study-wide significance (p < 3.16 × 10… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 67 publications
3
69
0
3
Order By: Relevance
“…In keeping with in vitro and animal studies, data from large-scale metagenome genome-wide association studies (mgGWAS) for the oral microbiome revealed unequivocal human genetic loci associated with the oral microbiome, including uric acid transporter SLC2A9. SLC2A9 showed a strong correlation with species-level clusters belonging to oribacterium and lanchnoanaerobaculum in tongue dorsum samples ( 83 ). A previous study reported that oral cavity and stool bacteria overlapped in more than 45% of subjects ( 84 ).…”
Section: Crosstalk Between Intestine Flora and Uric Acid Transportersmentioning
confidence: 99%
See 1 more Smart Citation
“…In keeping with in vitro and animal studies, data from large-scale metagenome genome-wide association studies (mgGWAS) for the oral microbiome revealed unequivocal human genetic loci associated with the oral microbiome, including uric acid transporter SLC2A9. SLC2A9 showed a strong correlation with species-level clusters belonging to oribacterium and lanchnoanaerobaculum in tongue dorsum samples ( 83 ). A previous study reported that oral cavity and stool bacteria overlapped in more than 45% of subjects ( 84 ).…”
Section: Crosstalk Between Intestine Flora and Uric Acid Transportersmentioning
confidence: 99%
“…A previous study reported that oral cavity and stool bacteria overlapped in more than 45% of subjects ( 84 ). Interestingly, the tongue dorsum microbiota related gene SLC2A9 was correlated with the abundance of Bifidobacterium animalis in the gut ( 83 ). These results demonstrated that gut microbial diversity also has an impact on uric acid transporters.…”
Section: Crosstalk Between Intestine Flora and Uric Acid Transportersmentioning
confidence: 99%
“…For instance, microbial communities in saliva and subgingival biofilms were found to have distinct ethnicity profiles, and based on these results, it was even possible to identify the ethnicity of individuals from subgingival microbial signatures using a machine learning classifier ( Mason et al, 2013 ). Furthermore, a recent metagenome-wide association study found that human genetics account for at least 10% of oral microbiome compositions between different individuals, which may also explain the stable microbial composition within one single individual over time ( Liu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The stability of the oral microbiota is dependent on both intrinsic host factors, such as the genetic composition of the host and aging [ 8 ]. It is also influenced by extrinsic host factors, such as drug use and lifestyle [ 9–11 ].…”
Section: Introductionmentioning
confidence: 99%